Diversity and Correlation Analysis of Sweet Potatoes (Ipomoea batatas L.) Resulting from an Open Cross with Beta-2 Female Parents for High Yield and Orange Flesh Color: Diversity and Correlation Analysis of Ipomoea batatas L. - Ratna Dewi; Mustika Adzania Lestari; Desi Maulida; Siti Novridha Andini; Septiana (Journal of Tropical Life Science, 2025)
Orange-fleshed sweet potatoes (OFSP) is rich in ß-carotene, an important source of pro-vitamin A. The availability of Orange-fleshed sweet potatoes varieties in Indonesia is still limited. For this reason, it is necessary to develop new and superior sweet potato varieties with an orange flesh color and high yielding. Crossing sweet potatoes is a fundamental method for producing new and diverse varieties. This study aimed to assess the diversity and kinship of sweet potatoes resulting from open crosses of 32 clones BOP at the Lampung State Polytechnic experimental garden in pursuit of high yields and orange flesh color. PCA, correlation analysis, and cluster analysis analyzed collected data. The results showed that 4 main components accounted for 72.80% of the total variance. Among the characteristics observed, the weight of large storage root, number of large storage roots, and weight of total storage root exhibited strong correlations, signifying their significant contributions to high diversity. Furthermore, 10 strains demonstrated high yield potential, namely BOP-1, BOP-3, BOP-4, BOP-6, BOP-8, BOP-33, BOP-36, BOP-42, BOP-43, and BOP-73 showcasing such traits. The cluster analysis of the 32 BOP clones, with a similarity level set at 65%, resulted in 4 distinct cluster groups based on the observed characteristics. The significant contribution to diversity, strong correlations among the traits, and cluster group differences among the clones have valuable implications for the selection in developing new sweet potato varieties process. Therefore, the selection process can be more efficient and effective.